Foul days - Dimova, Genoveva (Dimova, Genoveva. Witch's compendium of monsters, 2024)
"The Witcher meets Naomi Novik in this fast-paced fantasy rooted in Slavic folklore, from an assured new voice in genre fiction. As a witch in the walled city of Chernograd, Kosara has plenty of practice treating lycanthrope bites, bargaining with kikimoras, and slaying bloodsucking upirs. There's only one monster she can't defeat: her ex, the Zmey, known as the Tsar of Monsters. She's defied him one too many times and now he's hunting her. Betrayed by someone close to her, Kosara's only choice is to trade her shadow--the source of her powers--for a quick escape. Unfortunately, Kosara soon develops the deadly sickness that plagues shadowless witches--and only reclaiming her magic can cure her. To find it, she's forced to team up with a suspiciously honorable detective. Even worse, all the clues point in a single direction: To get her shadow back, Kosara will have to face the Foul Days' biggest threats without it. And she's only got twelve days. But in a city where everyone is out for themselves, who can Kosara trust to assist her in outwitting the biggest monster from her past?"--